2016 Florida Blueberry Integrated Pest Management Guide - Jeffrey G. Williamson; Philip F. Harmon; Oscar E. Liburd; Peter Dittmar (EDIS)
This revised 37-page fact sheet provides extensive information about integrated pest management for growing blueberry plants in Florida. Written by Jeffrey G. Williamson, Philip F. Harmon, Oscar E. Liburd, and Peter Dittmar, and published by the Horticultural Sciences Department, March 2016.